2014
DOI: 10.1177/0160323x14564470
|View full text |Cite
|
Sign up to set email alerts
|

The Microfoundations of Policy Inertia

Abstract: It is widely acknowledged that a key cause of the Community Development Block Grant (CDBG)'s longevity is its feedback effect on federal policy making via the creation of a large coalition of beneficiaries. Much less is known about the ''microfoundations'' of this self-perpetuating logic, namely, the city-level mechanisms directing local preferences toward preserving the grant. As a first attempt to fill this gap, this article identifies three such mechanisms and tests them on the cases of Arlington, VA, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…After the first decade of the CDBG program's existence, Wong and Peterson (1986) remarked on the redistributive nature of the program by noting that in Milwaukee, WI, and Baltimore, MD, neither city had spent more than 10 percent of its CDBG funds on redistributive policies. Tortola (2015), in a most-different case study analysis of Arlington, VA, and Baltimore, MD, found that policy inertia influenced the spatial allocation of CDBG funds. This policy inertia resulted in part from grant dependence of communities and clique networks (participants in the policymaking process).…”
Section: Social Equity and The Cdbg Programmentioning
confidence: 99%
“…After the first decade of the CDBG program's existence, Wong and Peterson (1986) remarked on the redistributive nature of the program by noting that in Milwaukee, WI, and Baltimore, MD, neither city had spent more than 10 percent of its CDBG funds on redistributive policies. Tortola (2015), in a most-different case study analysis of Arlington, VA, and Baltimore, MD, found that policy inertia influenced the spatial allocation of CDBG funds. This policy inertia resulted in part from grant dependence of communities and clique networks (participants in the policymaking process).…”
Section: Social Equity and The Cdbg Programmentioning
confidence: 99%
“…Integrating greater participation paradoxically leads to a perceived increase in accountability pressure on administrators to adhere to participant preferences. On the other hand, failure to ensure open processes and bring about greater public salience leads to further entrenchment of historical CDBG beneficiaries (Tortola, 2015). Therefore, the procedural mechanisms to include or exclude the public may have implications for other dimensions of polycentric social equity, such as access, quality, and outcomes.…”
Section: Application Of the Polycentric Social Equity Framework: The ...mentioning
confidence: 99%
“…To be successful, thinking must also shift: rather than assimilate new information and teamwork strategies into their existing organizing frameworks, partners must accommodate, or change their cognitive schemas (Block, 1982) and consider how to bring in new community networks (Tortola, 2015). Real change comes when group members reconfigure their psychological routines and schemas about collaboration, leading to an evolution in how they collaborate.…”
Section: Implementation: Agenda Sharing and Continuous Communicationmentioning
confidence: 99%
“…In this community example, the funding opportunity helped to identify project champions; the DHHS proposal was expected to address funding shortfalls within the community; and publicity around the high rate of teenage pregnancy drove a sense of urgency. County governments can capitalize on similar environments to strengthen collaboration and network partner performance through skilled staffing, coordinate effective communication among partnering organizations (Knepper, 2012), proactively recruit new collaborators rather than sustain familiar provider partnerships (Tortola, 2015), and foster nonprofit capacity (MacIndoe, 2013). The Teen Pregnancy and Parenting CI, however, suggests that public agency officials need the foresight to better predict when funder expectations will conflict with the emerging collaborative's capacity to fulfill all five conditions of CI.…”
Section: Conclusion: Policy and Social Context Mattermentioning
confidence: 99%